PENERAPAN MODEL PEMBELAJARAN TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X SMA NEGERI 2 TAMBANG - Rahmawaty '; Rasmiwetti '; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is about the application of cooperative learning model Two Stay Two Stray (TSTS) type that has conducted to know the increasing of student’s learning achievement on atom structure and chemical element periodic system topic in class X at SMA N 2 Tambang. This research was experiment by design pretest and posttest. The sample determined nonrandomly after doing normality and homogeneity test of 9 classes as population and then class X.4 as experiment group and X.5 as control group. The experiment group was applied by the application of cooperative learning model Stay Two Stray (TSTS) type. The data analysis technique used was t - test. Based on the tabulation of last data obtained tcount> ttable was 3,33 > 1.68 meant that the application of cooperative learning model Two Stay Two Stray (TSTS) type could increase the student’s learning achievement on atom structure and chemical element periodic system topic in class X at SMA N 2 Tambang. Keywords : TSTS, Cooperative Learning, Learning  achievement, atom structure and chemical element periodic system.